Future Development of Price Instruments of State Support for the use of Renewable Energy Sources in Kazakhstan - Tasmaganbetov, Aslan B.; Ðšunurkulzhayeva, Gulnar T.; Imanbayeva, Zauresh O.; Ataniyazov, Zhumabay; Shaikin, Dinmukhammed N. (International Journal of Energy Economics and Policy, 2019)
The article investigates various tools of state support for the development of renewable energy. Special attention is paid to the price instruments of state support for the use of renewable energy sources (RES), including a significant analysis of the regulatory framework of the Republic of Kazakhstan as incentives. The authors analyzed the level of development of fixed rates for the supply of electricity in the Republic of Kazakhstan. The analysis revealed that fixed rates had and continue to have a significant positive impact on the increase in projects for renewable energy. Without the use of this tool in Kazakhstan, it would not have been possible to establish such large RES capacities. The article also deals with the auction system of pricing for the supply of electricity. According to the authors, through the introduction of the auction mechanism, the state selects the most effective RES projects and forms market competitive prices for electric energy produced by RES facilities. Keywords: renewable energy sources, fixed rate, auction price JEL Classifications: Q21, Q28 DOI: https://doi.org/10.32479/ijeep.8481